2014
DOI: 10.1155/2014/934154
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Fatty Acid Composition and Distribution of N-3 Fatty Acids in Goat Tissues Fed Different Levels of Whole Linseed

Abstract: The effects of feeding different levels of whole linseed on fatty acid (FA) composition of muscles and adipose tissues of goat were investigated. Twenty-four Crossed Boer bucks were assigned randomly into three treatment diets: L0, L10, or L20, containing 0%, 10%, or 20% whole linseed, respectively. The goats were slaughtered after 110 days of feeding. Samples from the longissimus dorsi, supraspinatus, semitendinosus, and subcutaneous fat (SF) and perirenal fat (PF) were taken for FA analyses. In muscles, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Inclusion of sources of PUFA in animal diets comes mainly to increase these beneficial FA in animal products. In our previous studies, it has been reported that inclusion of whole linseed in diets resulted in increasing the proportion of ALA and total n-3 PUFA in goat muscles and adipose tissues as the inclusion level of linseed increased ( Abuelfatah et al., 2014 ). The growth performance and apparent digestibility were not affected by inclusion of linseed at level of 10% or 20%; however, at the level of 20%, the feed intake was negatively affected ( Abuelfatah et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion of sources of PUFA in animal diets comes mainly to increase these beneficial FA in animal products. In our previous studies, it has been reported that inclusion of whole linseed in diets resulted in increasing the proportion of ALA and total n-3 PUFA in goat muscles and adipose tissues as the inclusion level of linseed increased ( Abuelfatah et al., 2014 ). The growth performance and apparent digestibility were not affected by inclusion of linseed at level of 10% or 20%; however, at the level of 20%, the feed intake was negatively affected ( Abuelfatah et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, linseed contains a lower concentration of LA and saturated FA (SFA) compared with other oilseeds such as soybeans, cottonseed, corn, and sunflowers ( Maddock et al., 2005 ). Numerous studies have been undertaken to enhance n-3 PUFA content in ruminant meat and milk by feeding linseed ( Abuelfatah et al., 2014 ). However, reports documenting the effects of feeding whole linseed on ruminal microorganisms are rare.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of rich sources of PUFA in the diet of ruminants has shown increases in the concentration of omega-3 PUFA in meat and milk [14,96]. The type and source of PUFA consumed by the animal can have different impacts on microbial populations and rumen fermentation [97].…”
Section: Meta-regressionmentioning
confidence: 99%
“…Research indicates that the ratio of n6 to n3 FAs depends mainly on nutrition. Several studies have reported ratios in the range of 1.85 to 11.4 (Santos-Silva et al, 2002;Jerónimo et al, 2009;Ponnampalam et al, 2009;Abuelfatah et al, 2014). The reason for the higher ratio in lambs in this experiment is the use of soybean meal in feeding.…”
Section: Discussionmentioning
confidence: 71%